PENGUATAN KELOMPOK USAHA BERSAMA (KUB) PERIKANAN TANGKAP(STUDI KASUS DESA LATUHALAT,KOTA AMBON,PROVINSI MALUKU) - Lilian Sarah Hiariey; Nesti Rostini Romeon (LPPM Universitas Terbuka, 2017)
The Collective Business Group (KUB) of fisheriesVillage Latuhalat is a new step in the fishing community toimprove the welfare of living independently.because most of the population depend for their on the earnings of the sea and exposed tothe problem of poverty.Therefore, it is necessary to finda strategy which leads to an increase in the role of public institutions by strengtheningresearchKUBaims: 1) Assess the capacity of KUB's fisheries in promoting member; 2) Identify the factors that can support and hinder the strengthening of KUB fisheries and 3) Develop strategies and programs to strengthen KUB's fisheries.Qualitative research methods using technical methodsof Participatory Rural Appraisal (PRA). Results showed thatKUB constraints and needs in developing fisheries catch.Factors that hamper the strengthening of KUB are: (1) The condition of the community, (2) business improvement member is not yet optimal; and (3) the Government in granting program is participatory and KUB yet untapped to empower fishermen. Supporting factors, among others: (1) The fishery potential is quite large; (2) the establishment of institutional KUB Risna and Sibu-Sibu; (3) the availability of Fish Landing Ports (PPI) as a production catches;(4) Support Government policy through an increase in fish production.While inhibiting factor among others: (1) production decreased catches; (2) The fishermen have consumptive life pattern; (3) do not have the skills to process the fish when the fish are abundant; (4) the implementation of organizational management and production operations management low arrest. KUB proposed strategies can include: (1) Increasing the capacity of members and administrators; (2) Mentoring institutional management; (3) The development of networking; (4) Procurement of technical training arrests; (5) The assistance promotion in the management of fishery resources based local wisdom; and (6) Acquisition of facilities and infrastructure arrests.Kelompok Usaha Bersama (KUB) perikanan tangkapdi Desa Latuhalat merupakan satu langkah baru dalam masyarakat nelayan untuk mengembangkan kesejahteraan hidup secara mandiri. Sebagian besar masyarakat desa tersebut menggantungkan kelangsungan hidupnya dari penghasilan laut dan dihadapkan pada masalah kemiskinan. Perlu dicari strategi yang mengarah pada peningkatan peranan lembaga masyarakat melalui penguatan KUB. Penelitian ini bertujuan untuk: 1) Mengkaji kapasitas KUB perikanan tangkap dalam meningkatkan usaha anggota; 2) Mengidentifikasi faktor-faktor yang dapat mendukung dan menghambat penguatan KUB perikanan tangkap; dan 3) Menyusun strategi dan program penguatan KUB perikanan tangkap. Metode penelitian menggunakan metode kualitatif teknis Participatory Rural Appraisal (PRA). Hasil penelitian menunjukkan adanya kendala dan kebutuhan KUB dalam mengembangkan usahaperikanan tangkap. Faktor-faktor yang menghambat penguatan KUB adalah: (1) Kondisi komunitas, (2) Belum optimalnya peningkatan usaha anggota; dan (3) Pemerintah dalam pemberian program belum bersifat partisipatif dan KUB belum dimanfaatkan untuk memberdayakan nelayan. Faktor-faktor pendukung, antara lain: (1) potensi perikanan tangkap cukup besar; (2) terbentuknya kelembagaan KUB Risna dan Sibu-Sibu; (3) tersedianya Pelabuhan Pendaratan Ikan (PPI) sebagai tempat produksi hasil tangkapan; (4) Dukungan kebijakan Pemerintah Daerah melalui program peningkatan produksi perikanan. Sedangkan Faktor-faktor penghambat antara lain: (1) produksi hasil tangkapan menurun; (2) nelayan memiliki pola hidup konsumtif; (3) Nelayan tidak memiliki ketrampilan dalam mengolah ikan saat ikan melimpah; (4) penerapan manajemen organisasi dan manajemen operasi produksi penangkapan rendah. Strategi yang dapat diusulkan KUB antara lain: (1) Peningkatan kapasitas anggota dan pengurus; (2) Pendampingan manajemen kelembagaan; (3) Pengembanganjejaring; (4) Pengadaan pelatihan teknis penangkapan; (5) Pendampingan danpromosi dalam pengelolaan sumberdaya perikanan berbasis kearifanlokal dan (6) Pengadaan sarana dan prasarana penangkapan.